Controle inibitório do padrão de expiração ativa em ratos - Flor, Karine Correa (2018)
Late-expiratory neurons (late-E) located in the parafacial respiratory group (pFRG), a critical region for the emergence of active expiratory pattern, are conditional and remain silent at baseline conditions. In situations of metabolic challenges, these neurons become active and contribute to increase the abdominal motor activity during the late expiratory phase. It was found that late-E neurons are silent at rest due to inhibitory inputs. Interestingly, in conditions of sustained hypoxia (SH), commonly observed in people moving to high altitudes, this inhibitory drive is reduced and generates the active expiratory pattern. In the present study we hypothesized that the Bötzinger complex (BötC), located in the ventral respiratory column, plays an important inhibitory role on the emergence of active expiration. We also explored the possibility that BötC inhibitory mechanism is reduced after SH and the activation of this mechanism is able to normalize the expiratory pattern of SH rats. The aim of the present study was to explore the contribution of the BötC neurons in the generation of the active expiratory pattern in control and SH (10% O2, 24 h) rats. To reach this goal, we recorded the pulmonary ventilation (in vivo) and respiratory motor activity in in situ preparations of juvenile rats (60-80 g) to evaluate, under normocapnic and hypercapnic (8-10% CO2) conditions: i) activity patterns of BötC post-I (n=5) and aug-E (n=9) neurons of control rats; ii) changes in the respiratory pattern after BötC pharmacological disinhibition of control rats with gabazine (GABAA receptor antagonist, 250 μM, n=7) or strychnine (glycine receptor antagonist, 10 μM, n=7); iii) the respiratory pattern of SH rats in situ (n=7) and in vivo (n=12); iv) effects on the respiratory motor activity of control (n=7) and SH rats (n=7) after microinjections of L-glutamate in BötC (10 mM); v) changes in respiratory pattern of SH rats (n=8) promoted by the pharmacological disinhibition of the BötC with strychnine (10 μM). In control rats, post-I and aug-E neurons were recorded under hypercapnia (8% CO2). Hypercapnia evoked late-E activity in the abdominal nerve (AbN), in association with a decreased post-I activity and augmented aug-E activity. Regarding to the bilateral microinjections of gabazine in the BötC of control rats, we observed a decrease in baseline phrenic nerve (PN) bursts frequency and increases in the expiratory time and in the AbN activity, with the emergence of late-E bursts. On the other hand, bilateral microinjections of strychnine in the BötC of control rats diminished the PN, vagus (cVN) and AbN nerve amplitudes, but did not modify the 3-phase respiratory pattern; and attenuated the emergence of the active expiratory pattern under hypercapnia conditions. Concerning the basal ventilatory pattern of unanesthetized SH rats, we observed an increase in minute ventilation, associated with a higher respiratory frequency and tidal volume. These findings obtained in in vivo parallel with our data from in situ preparations, showing that SH evoked active expiratory pattern at baseline conditions. BötC stimulation of SH rats with L-glutamate was able to briefly abolish AbN late-E activity. In addition, BötC disinhibition of SH animals with strychnine eliminated the late-E AbN firing and restored the respiratory motor pattern, similarly to control animals. Taken together, our results indicate that BötC perform a relevant inhibitory role on the mechanisms of active expiratory pattern generation. In addition, short-term SH seems to change the activity of BötC neurons, reducing this inhibitory drive and contributing to the emergence late-E AbN activity at resting conditions in these animals.